The Benefit of Montelukast in Atopic Dermatitis Induced by Food Allergies - Isaac Melamed; Lacey Robinson; Melinda Heffron (Global Journal of Allergy - Peertechz Publications, 2017)
Background: Cysteinyl leukotriene levels are elevated in patients with atopic dermatitis, which can lead to eosinophilic infiltration of the gastrointestinal tract.  Objective: We examined the role that montelukast (a leukotriene receptor antagonist) might play in improving symptoms of atopic dermatitis induced by food allergies. Methods: We conducted a randomized, double-blind, placebo-controlled, parallel group study in 20 children, aged 1 to 8 years, with 4 study visits every 3 weeks for 9 weeks. Primary inclusion criteria consisted of: 1) positive reactivity to food (indicated by skin or RAST test); 2) 10-25 % body area affected with atopic dermatitis; and 3) gastrointestinal symptoms. Liquid cetirizine and 1% hydrocortisone cream were both given as rescue medications for atopic dermatitis flare-ups. Pruritis and atopic dermatitis flare-up scores were used to collect clinical data. Laboratory values for nerve growth factor were evaluated pre- and post-treatment.  Results: Our main endpoints were the effects of montelukast on the clinical presentation of atopic dermatitis. When comparing the treatment group to placebo, we noted a significant reduction in the pruritis score (p=0.002); a trend toward a reduction in the use of rescue medication (cetirizine: p=0.056; hydrocortisone cream: p=0.056); and a reduction in the level of nerve growth factor; mean values: placebo=3.06 to montelukast=2.59. Conclusion: The inflammatory pathway triggered by food allergies that may lead to atopic dermatitis can be modulated with montelukast. Furthermore, nerve growth factor may play a role in the pathogenesis of atopic dermatitis and montelukast may modify this pathway.